KATP channels and cardioprotection - Taskin, Eylem; Samper, Natalie; Yang, Hua-Qian; Nakamura, Tomoe Y; Ramasamy, Ravichandran; Coetzee, William (Archives of Pharmacy, 2024)
This review discusses ATP-sensitive potassium (KATP) channels, which connect intracellular energy metabolism to cellular electrical activity and play crucial roles in various physiological processes, particularly in the pancreas and cardiovascular system. KATP channels open when ATP levels decrease during metabolic stress, such as ischemia, helping to protect the heart from injury by maintaining membrane potential and preventing calcium overload. These channels are found in multiple cell types across the cardiovascular system, influencing vascular tone and cardiac excitability. The review highlights the need for further research into the specific expression of KATP channel subunits in humans and the consequences of ischemic events on their functionality. Additionally, it explores the interplay between glycolysis and KATP channels, suggesting that glycolytic ATP can modulate KATP channel activity while emphasizing the cardioprotective effects during ischemic events. The potential for KATP channel openers (KCOs) as therapeutic agents for ischemic heart disease is noted, particularly in improving outcomes in patients undergoing cardiac procedures. Challenges remain in developing specific KCOs with minimal side effects, but advances in precision medicine may enhance targeted therapies in the future. Overall, KATP channels represent promising targets for enhancing cardiovascular health.